Conductometric Titration of Metformin in Pure Form and in Pharmaceutical Preparations Using Sodium Tetraphenylborate and Cetylpyridinium Bromide - Abou-Dan, M.; Ashour, S.; Abou-Dan, H. (Asian Journal of Chemistry, 2010)
A sensitive and accurate conductometric method for the determination of 0.4-8.5 mg of metformin hydrochloride (MetHCl) using sodium tetraphenylborate (TPB) and cetylpyridinium bromide (CPB) in aqueous solution is described. The effect of the solvent, reagent concentration, temperature and time on the shape of the titration curve was studied. Statistical treatment of the experimental results indicates that the method is precise and accurate. The accuracy of the method is indicated by the excellent recovery (99.5- 100.9%) and the precision is supported by the low standard deviation < 0.06. A comparative study between the suggested procedure and the pharmacopoeial method for this compound in its pharmaceutical preparations showed no significant difference between the two methods.